Diagnoza osiągnięcia dwujęzyczności u dzieci migrantów: etapy przyswajania języka drugiego i metody oceny kompetencji językowych - Kushnir, Valentyna (Studia Edukacyjne, 2026)
The contemporary school and psychological and pedagogical counseling center increasingly face the challenge of effectively diagnosing children with migration experience who operate in the context of bilingualism and multiculturalism. This article attempts to discuss the fundamental issues related to assessing the level of second language (L2) acquisition (Polish) in migrant children. The article presents the differences between formal language learning and natural language acquisition, characterizes the classical stages of second language development, and emphasizes the need to consider factors such as the child’s length of stay in the country, exposure to the Polish language, and the level of development of the first language (L1). Particular attention is paid to the variation in language competencies in the areas of listening comprehension, speaking, reading, and writing, as well as to the difficulties in their diagnostic interpretation. The importance of differential diagnosis is also highlighted, as it allows to distinguish natural language difficulties from symptoms of specific learning disorders (SLD), along with the significance of interdisciplinary cooperation among specialists, parents, and teachers. The authors refer to contemporary concepts proposed by scholars such as Cummins, Krashen, Pamuła, Błasiak-Tytuła, and Łuniewska, emphasizing the need for a careful, culturally sensitive, and individually tailored diagnosis of bilingual children.